Spanish Dictionary of Definitions - A. Fuertes-Olivera, Pedro; Bergenholtz, Henning (Círculo de Lingüística Aplicada a la Comunicación, 2018)
Dictionaries for text reception are information tools that are designed and constructed for helping users (both humans and machines) to decode both oral and written texts. The diccionario español de definiciones is one of these information tools. It has been designed under the tenets of the Function Theory of Lexicography and it is currently under construction (it already has around 80,000 entries). It will be part of Diccionarios Valladolid-UVa, a dictionary portal designed and constructed with funds and resources from the universities of Aarhus and Valladolid, as well as the Danish company Ordbogen A/S. This dictionary aims to fill a gap in the Spanish lexicographical landscape in which dictionaries such as these do not exist, perhaps because the so-called “diccionario general definitorio” (general defining dictionary) is rather common. Our dictionary is rather different from existing ones and puts into practice some new concepts and ideas: (a) discussions about meaning are irrelevant for lexicography; (b) lexicographic data must be “correct”, but “correct” and “true” are not synonymous; (c) data selection and inclusion must be based on users’ needs, especially for avoiding information overload; online dictionaries are dynamic information tools containing dynamic articles with dynamic data; (e) such a dictionary type can only de designed by constructing its own dictionary-writing system, which must be composed of its own editor, search engine and interface. To the best of our knowledge, existing commercial dictionary writing suites do not allow the construction of dynamic dictionaries.
Keywords: Definition; Function Theory of Lexicography; Online dynamic dictionary; Spanish